The acquisition of technical terms using the online learning approach among aircraft maintenance learners - Jeremy Ivan Thambirajah; Pramela Krish; Azianura Hani Shaari (Penerbit Universiti Kebangsaan Malaysia, 2022)
Building a good understanding of the technical terms is an essential achievement for aircraft maintenance learners for their future careers in the field of aircraft maintenance. With the recent evolution in educational technologies, teaching and learning technical terms need to be shaped differently. Most studies on technical terms acquisition have been conducted at college levels via the traditional mode. Hence, this qualitative study explored the implementation of the online learning approach as a medium to learn technical terms. Data were collected from in-depth interviews as well as online observations with fourteen first-year aircraft maintenance learners on how the online platform assists in acquiring technical terms. Additional data was obtained from the instructor teaching them. The results of the interview indicated that the learners improved on their technical terms acquisition in four significant aspects such as blended learning, group learning, the role of the lecturer and the utilisation of an online dictionary. Learners also reported that the implementation of the online learning approach enabled collaboration between the lecturer and the learner to improve their online learning experiences. The results presented a much-needed and currently lacking, view into the actual use and the online learning approach for technical terms acquisition among aircraft maintenance learners in this private university.